Uranium enrichment associated with geothermal alteration: An example from Rehai, Tengchong volcanic area of China - Li, Rong (Geological journal (Chichester, England), 2022)
For the continental rift‐related geothermal system, the hydrothermal alteration zones are rarely studied for uranium exploration. High uranium concentrations (up to 36 ppm) are shown in the altered sandstones at the Rehai geothermal field (RHGF) in Tengchong, China. To demonstrate the uranium enrichment mechanism, this study comparatively examines the trace element (uranium in particular) and rare earth element (REE + Y) concentrations of hot spring water, spring deposits (sinters and sulphates), and altered host sandstones from the RHGF of the Tengchong volcanic area. Along the central north‐south trending fault at Rehai, sinters and sulphates are precipitated from hot spring water, and the Neogene sandstones have been altered by hydrothermal fluids into zones formed of various clay minerals. The δD and δ18O values for the hot spring water indicate that the geothermal water originates from meteoric water. The spring water and hot spring deposits have identical REE distribution patterns which are featured with heavy REE (HREE) enrichment and negative Eu anomalies. Among the hot spring deposits, the yellowish earthy aggregates (tamarugite) deposited at the acidic Zhenzhu Spring have the maximum U concentration (27 ppm). The altered sandstones at Rehai, however, display the highest U concentrations (14–36 ppm). The U enrichment in the hot spring deposits and altered host rocks at the Rehai geothermal field is probably related to the multiple cycles of uranium leaching from granites, transportation upward along fault structures by geothermal water, decompression, and fixation in the hot spring deposits and/or alteration products. The results indicate that alteration zones associated with geothermal systems are also potential targets for uranium exploration. We investigate the uranium enrichment in the hot spring deposits (sinters and sulphates) and hydrothermal alteration zones (formed of clay minerals) in the Rehai geothermal field, Tengchong volcanic area. The alteration zone associated with the geothermal system is a potential exploration target for uranium mineralization.